Development of porous calcium phosphate bioceramics for bone implant applications: a review - Naqshbandi, Abreeq R.; Sopyan, Iis; -, Gunawan (Bentham Science, 2013)
The present review briefly outlines the most recent patents and journals on various aspects of porous calcium phosphate bioceramics including techniques of preparation, properties and bone implant applications. Bioactive ceramics are a class of materials that have capability to bond directly with the host bone. These materials can be easily assimilated by the body and are considered to be biodegradable. Researches have revealed that artificial bones made from hydroxyapatite or a combination of hydroxyapatite (HA) and tricalcium phosphate (TCP) is a perfect substitute for natural bone owing to its excellent biocompatibility and properties close to that of human bone. Bioceramics made of HA are available in dense and porous forms. Several efforts on the fabrication of porous calcium phosphate bioceramics have been carried upon in the field of clinical orthopaedics. The realisation of these efforts can be observed from the fact that numerous patents have been filed on methods of preparing porous calcium phosphate bioceramics for bone implant applications. A number of porous HA ceramics have been developed for applications in both tissue engineering and drug delivery systems. Porous bodies are decomposable in human body and provide a surface for proliferation and growth of cells that are infiltrated from the surrounding tissues so that a new bone grows into the pores and prevents any movement or loosening of the implants. Consequently, these can be used for filling the damaged bone, repair of fractured bone and even can be used as hard tissue replacements. Several processing techniques have been employed for fabrication of porous scaffolds. Among prominent techniques are gel casting, slip casting, camphene-based freeze casting and polymeric-sponge method.